Serum carbohydrate antigen 19-9 represents a marker of response to neoadjuvant therapy in patients with borderline resectable pancreatic cancer - Tzeng, Ching-Wei D (Blackwell Publishing Ltd, 2014)
OBJECTIVES: The purpose of this study was to determine the relationship between carbohydrate antigen (CA) 19-9 levels and outcome in patients with borderline resectable pancreatic cancer treated with neoadjuvant therapy (NT). METHODS: This study included all patients with borderline resectable pancreatic cancer, a serum CA 19-9 level of ≥40 U/ml and bilirubin of ≤2 mg/dl, in whom NT was initiated at one institution between 2001 and 2010. The study evaluated the associations between pre- and post-NT CA 19-9, resection and overall survival. RESULTS: Among 141 eligible patients, CA 19-9 declined during NT in 116. Following NT, 84 of 141 (60%) patients underwent resection. For post-NT resection, the positive predictive value of a decline and the negative predictive value of an increase in CA 19-9 were 70% and 88%, respectively. The normalization of CA 19-9 (post-NT <40 U/ml) was associated with longer median overall survival among both non-resected (15 months versus 11 months; P = 0.022) and resected (38 months versus 26 months; P = 0.020) patients. Factors independently associated with shorter overall survival were no resection [hazard ratio (HR) 3.86, P < 0.001] and failure to normalize CA 19-9 (HR 2.13, P = 0.001). CONCLUSIONS: The serum CA 19-9 level represents a dynamic preoperative marker of tumour biology and response to NT, and provides prognostic information in both non-resected and resected patients with borderline resectable pancreatic cancer.